Bryophytes in coenoses of “Opuksky” Nature Reserve (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
The articles present a checklist of Opuksky Nature Reserve mosses, which includes 49 species, 5 forms, 6 varieties. The structural features of bryoflora is briefly reviewed.
Keywords: list of mosses, Opuksky Nature Reserve, Crimean Plane.